2013
DOI: 10.2320/matertrans.mi201216
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Kinking of the Long-Period Stacking/Order (LPSO) Phase in a Hot-Extruded Mg<sub>97</sub>Zn<sub>1</sub>Y<sub>2</sub> Alloy

Abstract: Microstructures of a hot-extruded Mg 97 Zn 1 Y 2 alloy containing the long-period stacking/order (LPSO) phase have been investigated by transmission electron microscopy (TEM), particularly focusing on kink-deformed LPSO crystals. It is found that kink-deformation in the LPSO phase grains are mostly characterized by singular straight interfaces across which the host crystals are sharply bended, as being similar to those reported previously. In addition to these common LPSO phase kink-bands, we occasionally find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…At 40 N, in the mild wear regime, a deformation zone of about 220 μm thickness was formed beneath the surface (Figure 9a), while Mg 12 ZnY strips could coordinate with the deformation of α-Mg dendrites by bending or by forming kinks from the magnification microphotograph (Figure 9b). It was reported that the kink bands developed when compressive stress was loaded parallel to the (0001) plane—i.e., basal slippage was inhabited—and they could contribute to some extent to the ductility of the Mg97Zn1Y2 alloy [22]. When the load was increased to 100 N under the severe wear regime, a DRX zone of about 40 μm thickness was formed, followed by a plastic deformation zone of about 120 μm thickness underneath (Figure 9c).…”
Section: Resultsmentioning
confidence: 99%
“…At 40 N, in the mild wear regime, a deformation zone of about 220 μm thickness was formed beneath the surface (Figure 9a), while Mg 12 ZnY strips could coordinate with the deformation of α-Mg dendrites by bending or by forming kinks from the magnification microphotograph (Figure 9b). It was reported that the kink bands developed when compressive stress was loaded parallel to the (0001) plane—i.e., basal slippage was inhabited—and they could contribute to some extent to the ductility of the Mg97Zn1Y2 alloy [22]. When the load was increased to 100 N under the severe wear regime, a DRX zone of about 40 μm thickness was formed, followed by a plastic deformation zone of about 120 μm thickness underneath (Figure 9c).…”
Section: Resultsmentioning
confidence: 99%
“…A decade ago, it was found that at the atomic Y/Zn ratio of 2, the strength of Mg-Zn-Y alloys can be greatly enhanced by the formation of an LPSO structure in which Y and Zn atoms are arranged periodically in the basal planes of magnesium, forming an ordered structure [7]. The main strengthening mechanism of the LPSO-containing Mg alloys has been proposed as a refinement and work hardening of LPSO during the kinking process [8,9]. More recently, attention has been focused on the dynamic recrystallization (DRX) and hot deformation behaviors of LPSO-containing Mg alloys [10][11][12][13][14], which is important to understand in order to determine the best conditions for their hot workability and achieving fine-grained and homogeneous microstructures after hot working.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23,30] Figure 1 shows high resolution Z-contrast images for tilt GBs in Mg matrix (a, c) and LPSO phases (b, d) in deformed Mg 97 Zn 1 Y 2 (at%) samples. Facecentered cubic (FCC) sub-blocks with higher concentration of solute atoms in the middle two layers on both sides of GBs connect continuously in both matrix (c) and LPSO phases (a, b, d) at the boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…For example, basal slip, pyramidal slip, solute segregation, stacking faults (SFs), and their interactions play critical roles in strengthening and toughening this kind of Mg alloys. [22][23][24][25][26][27] The contribution of GBs to ductility of this kind Mg alloys has not been investigated so far. Therefore, it is necessary to study sliding and migration of GBs, in order to obtain comprehensive understanding of deformation behavior, as well as the strengthening and toughening mechanisms in Mg alloys with LPSO phases.…”
mentioning
confidence: 99%